Peran Keadilan dan Sistem Perpajakan dalam Mengatasi Tantangan Penggelapan Pajak di Indonesia - Suvinah; Hafidzullah, Akhdan Yogie; Hendrawarman; Awangga, Raden Arief (HUMANIORUM, 2024)
This study explores the dynamics of tax evasion in Indonesia with a focus on the role of tax justice and the tax system. As a developing country, Indonesia faces challenges in increasing taxpayer compliance. Qualitative research methods and normative law are used to analyze the factors that influence taxpayer behavior regarding tax evasion. The research results highlight the importance of tax justice as a driver of taxpayer compliance. The benefit principle is the key to creating a positive perception of tax obligations. The self-assessment system, while encouraging active participation, opens up opportunities for tax evasion. Public awareness, reform of the tax system, and effective law enforcement were identified as solutions to overcome these challenges. This study provides an in-depth understanding of the complexity of the issue of tax evasion in Indonesia and offers views on strategic steps that can be taken by the government and society. By highlighting the role of tax justice and the importance of an effective tax system, this research contributes to the development of better tax policies and creates a fair and sustainable tax environment.